Improving Student’s Motivation and Learning Outcomes through Canva in English Learning at Middle Schools - Ferdian Rizki Pratama; Mauly Halwat Hikmat (Journal of English Language Teaching and Linguistics, 2024)
Increasing student motivation and learning outcomes can be done by utilizing technology in the learning process. The objective of this study was to describe students' perspectives on the use of the Canva in English class. The type of research was descriptive qualitative. The subjects of the study were students of class VIII of SMP Muhammadiyah 7 Surakarta. The sampling method used purposive sampling. Data collection techniques used questionnaires, observations, and interviews. Before the instrument was used, validation was carried out by experts (supervisors), and the collected data was validated using source triangulation and triangulation of data collection methods. Data analysis used qualitative analysis. The results of the study were: (1) Teachers use Canva in English classes for three reasons. First, to display learning materials interactively. Second, to create interesting worksheets. Third, for students to do assignments with Canva; (2) Students' perspectives on Canva as a mediua in English classes showed good results. Students agreed and gave positive responses regarding Canva as a media in learning English. Students agreed that Canva is a good mediua to use in learning English. The conclusion is that the use of Canva as a learning media can increase students' learning motivation and learning outcomes. The implication of the results of this study is that teachers can use the Canva application as a learning medium.